Cell identity specification in plants: lessons from flower development. (17th April 2021) - Xu, Xiaocai; Smaczniak, Cezary; Muino, Jose M; Kaufmann, Kerstin
Abstract : Cellular differentiation in plants integrates information from developmental history, position, and environment. We use flower development as a model system to introduce molecular mechanisms controlling cell type specification and cellular heterogeneity. Abstract: Multicellular organisms display a fascinating complexity of cellular identities and patterns of diversification. The concept of 'cell type' aims to describe and categorize this complexity. In this review, we discuss the traditional concept of cell types and highlight the impact of single-cell technologies and spatial omics on the understanding of cellular differentiation in plants. We summarize and compare position-based and lineage-based mechanisms of cell identity specification using flower development as a model system. More than understanding ontogenetic origins of differentiated cells, an important question in plant science is to understand their position- and developmental stage-specific heterogeneity. Combinatorial action and crosstalk of external and internal signals is the key to cellular heterogeneity, often converging on transcription factors that orchestrate gene expression programs.